Frequency of RNF213 p.R4810K, a susceptibility variant for moyamoya disease, and health characteristics of carriers in the Japanese population. Issue 5 (September 2016) - Cao, Yang; Kobayashi, Hatasu; Morimoto, Takaaki; Kabata, Risako; Harada, Kouji; Koizumi, Akio
Abstract Objectives RNF213 p.R4810K is a founder polymorphism that confers genetic susceptibility to moyamoya disease in East Asia. Only a few studies have investigated the symptoms and disease histories ofRNF213 p.R4810K carriers in Japan. This study investigated the frequency ofRNF213 p.R4810K in the general Japanese population and the health characteristics of the carriers. Methods Through a health-promotion campaign in the city of Uji, Japan, 519 subjects (120 males and 399 females) of the general Japanese population were genotyped forRNF213 p.R4810K and interviewed to determine health characteristics. Results NineRNF213 p.R4810K heterozygous carriers (GA genotype) and noRNF213 p.R4810K homozygous carriers (AA genotype) were found among the 519 individuals. The estimates of the genotypes and allele frequencies forRNF213 p.R4810K were 1.73 and 0.87 %, respectively. There were no obvious differences in age, gender ratio, body mass index, hypertension, dyslipidemia, diabetes, kidney disease, liver disease, heart disease, or drinking or smoking habits between carriers and non-carriers. Interestingly, one patient with moyamoya disease was found among the nineRNF213 p.R4810K carriers. Conclusions This study showed the genotypes and allele frequencies ofRNF213 p.R4810K in the general Japanese population to be similar to results of previous reports.